The notorious ESG : business, climate, and the race to save the planet - Shastry, Vasuki (Emerald Publishing Limited, 2023)
Environment, Social, Governance (ESG) has become the noun, verb, and adjective of the modern business era. Faced with societal and regulatory pressure, big business in America, Asia, and Europe has been forced to define and articulate ESG goals to combat climate change and save the planet. The only problem is that ESG has been captured by the PR hype machine as a few prominent business leaders make bold promises to save the planet but are vague about how they propose to achieve this. Eager to showcase their green credentials, companies are making all kinds of promises to reduce their carbon footprint and to play their part in reducing global warming and improving social outcomes. How to separate fact from fiction and exaggerated commitments from realistic goals? Vasuki Shastry spent several years at the coal face itself - running ESG for a major international bank in the City of London - and argues that corporate cultures are too focused on the profit motive and quarterly business targets. Change can only really come through a paradigm shift for business which aligns business with social purpose. Getting there will require a corporate revolution which will disrupt and dislodge the ancien régime and usher in a new age of sustainable business. The author offers a solution in the form of a Climate Manifesto for Business that will Make Our Planet Great Again!